PENGARUH GOOD CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY, DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN: (Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Industri Barang KonsumsiYang Terdaftar di Bursa Efek Indonesia) - Sudjana, Krisna; Agustini; Fatimah, Syifa (Jurnal Gici Jurnal Keuangan dan Bisnis, 2023)
The company's goal to improve the welfare of shareholders can be realized by maximizing corporate value which can be influenced by GCG, CSR and financial performance to company value. Company value is an investor's perception of a company, which is often linked to the stock price. High stock prices make the company's value also high. Company value is very important because it can describe the company's performance which will later influence investors towards the company so that it can help make financial decisions in investing funds in the company. In this study corporate governance is proxied into the principles of Corporate Government according to FCGI in the general guidelines of Corporate Governance Indonesia banking (KNKG, 2004), while for Corporate Social Responsibility (CSR) is proxied into Reporting based on the guidelines of the Global Reporting Initiative (GRI). The population in this study is 42 manufacturing companies in the consumer goods industry sector listed on the IDX. The sampling technique used was purposive sampling and a sample of 25 companies was obtained. The analysis technique used is multiple regression analysis. Data for this study was obtained from the company's annual report available on the Indonesia Stock Exchange (IDX). The tool used for this study was SPSS 23. The results of this study show that Good Corporate Governance (GCG), Corporate Social Responsibility (CSR) and Financial Performance do not have a significant effect on Company Value. Keywords: Good Corporate Governance, Corporate Social Responsibility, Financial Performance, Corporate Value.